Special issue the discourse of judging - Sarat, Austin (Studies in law, politics, and society ;, 2012)
This special issue of Studies in Law, Politics, and Society focuses on the discourse of judging and the "language of judging" within many diverse legal scenarios. The volume features chapters specifically on: the "language of rights" within the context of abortion and same-sex marriage cases; discourses within the European Court of Justice; the modern-day place of politics in the US Supreme Court; and discussions on the two-court crisis which lead to the US Constitutional Convention of 1849. The chapters question the complex and conflicting relationship between politics and the law, understanding judicial independence, and offer an analysis of how the literary narrative of law plays a significant part in the delivery of legal judgement.